Diagnóstico y planeación financiera a la compañía OFFICEGOLDEN S.A. de la ciudad Guayaquil en el periodo 2022 - 2025 - Vélez García, Roxana del Cisne (2022)
The following research work entitled "DIAGNOSIS AND FINANCIAL PLANNING OF THE OFFICEGOLDEN S.A. COMPANY IN THE CITY OF GUAYAQUIL THROUGH THE PERIOD 2022-2025" aims to fulfill the general objective which is to perform the diagnosis and financial planning in the company OFFICEGOLDEN S.A. during 2022-2025, in order to know its economic-financial situation. To accomplish the specific objectives, information was gathered through discussions with the manager and accountant of the organization. Additionally, to perform the financial diagnosis, through the application of financial tools such as vertical and horizontal analysis to determine the degree of participation and the behavior of the accounts of the financial statements; also applied the indicators of liquidity, activity, indebtedness and profitability, which allowed to determine that the company has adequate liquidity to develop its activities and weaknesses such as low turnover of its inventories. After carrying out the financial diagnosis, a report on the company's actual situation was issued. An increase of 9.59% in sales and purchases was projected for each projected year, taking into consideration that purchases also increased by the same percentage. The cash budget was prepared in order to forecast the future availability of cash. Once the projections were calculated, the pro forma financial statements were prepared, where the possible scenario for the following years is visualized. Based on the projected income statements, it was calculated the break-even point by separating fixed and variable costs, which showed how much OFFICEGOLDEN SA should sell in order to recover the investment made without making a profit